THE CONFLICT BETWEEN CERTAIN CAPITAL ALLOWANCES IN THE INCOME TAX ACT AND THE SPECIAL ECONOMIC ZONES POLICY OBJECTIVES - Waldette Anne Engelbrecht; Cecileen Greef; David Joubert; Shaun Parsons; Cara Thiart (Obiter, 2023)
Through various incentives, special economic zones (SEZs) aim to promote industrial capacity development, create jobs and stimulate the South African economy. However, in practice, misalignment of tax legislation requirements with current practices may undermine the success of the SEZ programme. If property developers are unable to claim capital allowances for expenditure incurred on property developments within an SEZ, this acts as a disincentive to investment, which conflicts with the overarching rationale for the SEZ initiative. This study seeks to determine the extent to which current practices prevent property developers from claiming capital allowances for developments in SEZs, and to propose appropriate remedies. The study presents a doctrinal analysis of the requirements of the SEZ Act and relevant provisions of the Income Tax Act in the context of current practices in SEZ development. The analysis demonstrates that, where the ownership of land designated for SEZ development is retained by government, property developer lessees may be unable to claim capital allowances in respect of expenditure incurred on property developments. This study therefore motivates for the removal of the ownership requirement from building allowance provisions of the Income Tax Act. This would align tax legislation with current practice and the policy objectives of the SEZ programme, as well as address the current inconsistency in the requirements of building allowances.